Reforma agrária no Brasil: uma análise do II PNRA como política de enfrentamento à questão agrária - SANTOS, Frednam Bezerra dos (2016)
The hypothesis that guides research is linked to the understanding that the land question in Brazil must be understood as a manifestation of the capitalist accumulation process which brings us to the debate on the state's role on the prism of reform or revolution. The relevance of the land question in Brazil is observed both in social conflicts in the countryside and in the economic dynamics of the Brazilian middle-rural determining the history of agrarian reform forward the advance of agribusiness. The history of land reform in Brazil must be understood in the light of social and blocking "political-legal-institutional" demands of these by the state ruling elites that materializes in the 1850 Land Law, the Land Statute in 1964, in the preparation of I NARP in 1985, land reform market established with the World Bank support in 1998, and in the "agribusiness strategy" when editing the NARP II in 2003. from an ideological political point of view liberalizing policy to combat poverty implemented in Brazil from the 1990s, with the support of the UN, fits the liberal strengthening market strategy. In this context, agrarian reform becomes a stopgap policy. In Brazil, the agrarian reform is only performed from the pressure of social movements. In terms of structure, the dissertation is organized into five chapters, and the first recover the debate on the roots of the agrarian question in Brazil taking the land, means of production, compared to subjects of the agrarian question as the central element for understanding the contradictions of capitalist development in the field. The second is discussed agrarian reform as a structural policy, recapitulated the political debate on the duality: reform or revolution within the framework of the contemporary capitalist state and the institutionalization of agrarian reform as a result of workers' struggle. In the third chapter rescues the historical process of land reform in Brazil with emphasis on blocking processes agrarian reform. The fourth chapter discusses the NARP II as a coping policy to the agrarian question in Brazil taking as a starting point the process of political construction ahead the political and economic power of agribusiness and confronts the results of II PNRA with the situation. But the analysis of the results of II PNRA points to its configuration as a sectoral policy of promoting family farming.